Dryland Wheat in Western Kansas (W-S-F Rotation) - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on typical production of wheat in western Kansas.
MF903_1995_10
Keywords: MF903; Economics; Crops; MF